Optimization of energy output from PVT-PCM systems with emerging metal-organic frameworks phase change materials - Bourhan Tashtoush; Malak Al Ghadi (Heliyon)
Existing literature has largely overlooked the challenge of providing continuous electrical and thermal energy solely through solar power, especially in rural areas with diverse energy demands. The current study investigated two configurations of photovoltaic thermal-phase change material systems: system A, which features water-based thermal collector tubes positioned above the phase change material layer, and system B, which has tubes situated below the phase change material layer. Originality is manifested in the exploration of two essential inquiries: (i) Can the generation of thermal energy during nighttime be optimized by modifying the geometric configuration of the layers within the solar energy system? (ii) In what manner do actual weather conditions, especially in desert compared to non-desert areas, influence the efficacy of these systems, considering the generally cooler nocturnal temperatures in deserts? The study evaluated the influence of the positioning of water-based thermal collectors in solar energy applications. Numerical simulations were conducted over a continuous 24-h duration under authentic natural conditions in two locations: Ma'an (a desert) and Irbid (a non-desert city). The study also examined the reaction of these systems to novel stearic acid metal-organic frameworks composite phase change material and evaluated the effects of varying flow rates. The maximum cumulative electrical power output for system A in Ma'an, utilizing a 3 cm thickness of phase change material, was determined to be 3095.81 W/day. The thermal energy levels in Irbid were generally greater than those in Ma'an. System A operated optimally in Irbid for continuous 24-h functionality, while system B excelled in Ma'an for thermal energy production. System B retained a greater amount of latent heat in the phase change material layer than System A. During the night hours, system B demonstrated considerable enhancements in water outlet temperature compared to system A, thereby improving night-time thermal energy output. Moreover, it was observed that elevated flow rates diminished latent heat storage in the phase change material layer and outlet water temperatures in both systems, while electrical power output was influenced by flow rate solely in system A. This study offers essential insights into optimizing configurations of photovoltaic thermal-phase change material systems and emphasizes the significance of accounting for geographical and climatic conditions to enhance system performance.